Interiörljus i lastbilshytt för fjärrtransportförare: Med avseende på välbefnnande - Axelsson, Ellinor; Liew, Caroline; Lööf, Gustaf; Marttila, Marcus; Osterman, Ida; Runeson, Lovisa (My University, 2023)
Long-haul truck drivers spend a lot of time in the truck cabin, since they drive, eat and sleep in it. Thus, the cabin becomes similar to a second home for the drivers. Therefore, it is important that they feel comfortable in the cabin and that it contributes to an increased well-being for the drivers. The interior light is a contributing factor to this and is therefore important to investigate, which the client Volvo Trucks has identified. The goal of the project was to create a comprehension of the problem with an associated list of requirements for the interior light in the truck cabin, to then develop a concept that corresponds to this. Based on user studies, observations, and literature studies, the three main aspects to fulfill in order to achieve the well-being of the drivers were personification, user-experience, and health. This resulted in the final LUMINA concept. In LUMINA, LED-strips are discreetly placed in the cabin to illuminate surfaces, creating an experience of increased space and coziness. To enable a personalized cabin, the color and intensity of the lights can be adjusted based on activity and preference. Furthermore, the light can gradually increase, similar to the natural daylight, to contribute to an improved circadian rhythm. In order to further develop the concept, more data collection and prototyping are of great significance. Since truck drivers are important for the future, further investigation in this area is of utmost importance.